Three-dimensional scour simulations with a two-phase flow model. (April 2020) - Nagel, Tim; Chauchat, Julien; Bonamy, Cyrille; Liu, Xiaofeng; Cheng, Zhen; Hsu, Tian-Jian
Highlights: The applicability of two-phase flow models to complex sediment transport problems like 3D scour around a vertical cylinder is demonstrated. A new methodology to determine the bed shear stress in complex flow configurations is proposed. Upstream of the pile, the dimensionless flux can deviates from the uniform and steady flows transport law by almost one order of magnitude. In the scour hole, the sediment flux results from a competition between the fluid bed shear stress and the downslope gravity effect. The downslope gravitational effect becomes significant at low bed slope angles, with a linear dependency of the sediment flux to the bed-slope angle below β  ≈ 23 ∘ and a nonlinear dependency above. Abstract: In this contribution, a three-dimensional sediment scour model based on the two-phase flow Eulerian-Eulerian solver, sedFoam, is developed within the framework of the open source platform OpenFOAM. The adoption of the Eulerian approach for both fluid and sediment makes the model suitable for simulating scour process around structures with arbitrary geometry. The model is first validated with unidirectional sediment transport configurations without structures, to ensure that it can capture both flow and sediment transport processes. The validation cases show that the model can accurately simulate the sediment transport rate and bedload layer thickness as a function of the Shields number over a wide range of flow condition and sediment properties. Then, the model is applied to simulate the live-bed scour process around a vertical pile due to unidirectional current. It is a first attempt to use a two-phase model for simulating such case and its success serves as a proof-of-concept for future development. Simulated results of flow, sediment transport, and scour processes are compared with experiments and good agreement is observed. A new methodology to determine the bed shear stress in complex flow configurations is proposed. The mixture shear stress computed at the elevation of the iso-concentration ϕ 0 = 0.08 (corresponding to top of the bedload layer) is used to define the local Shields number. Within the scour hole, a competition between fluid bed shear stress driven and gravity driven sediment transport occurs at bed angles up to β  ≈ 23 ∘ . This is lower than the repose angle ( β r = 32 ∘ ). The relationship between the sediment flux and the bed slope is linear below β  ≈ 23 ∘ . Above this angle the sediment flux increases nonlinearly with the bed slope while the Shields number tends to 0. This shows that, in the part of the scour hole close to the vertical cylinder, the sediment flux only result from the action of gravity: avalanching is the dominant transport mechanism and conventional power law become ineffective even with slope correction. In the lee-side of the cylinder suspended load dominant and the power law, assuming a local equilibrium between bottom shear stress and transport flux, is no longer valid. Further discussion is made on the computational cost of the proposed model and future research directions.